Feasibility of Air Conditioning (AC) Utilization as Heat Pump System for Fish Cracker Drying Machine - Adepradana, Cintopa Satria; Fudholi, Ahmad; Zurhalki, Muhammad (Balai Publikasi Indonesia, 2023)
Fish crackers are one of the most popular snacks in Southeast Asian countries, including Malaysia. Traditionally, the process of fish crackers drying usually uses sun drying method. The problem of this method is uncontrollable weather conditions. Drying of fish crackers requires an alternative in the drying process. The heat pump is the most effective and controllable alternative dryer in reducing the moisture content of the material. Air Conditioning (AC) is one type of heat pump. The heat produced by the AC condenser can be used to dry fish crackers. In this study, the AC utilization as a heat pump system to dry fish crackers has an Evaporate Capacity (EC) of 1,838kg/h, a Specific Moisture Extraction Rate (SMER) of 1,998kg/kWh, and a Specific Energy Consumption (SEC) of 0.425kWh/kg of dry crackers. This drying machine is also economically feasible because it has an NPV> 0 which is RM28201.58 with an investment period of 1 year.